Inverkan av nederbörd, temperatur och frost på årsringens egenskaper hos boreal tall (Pinus sylvestris L.) - Grape, Sofia (2007)
The wide distribution range of our boreal pine (Pinus sylvestris L.) provides a great variation in growing conditions and climate/weather factors that influence the wood development of the trees. A great number of extensive studies have been conducted over the years in order to clarify growth trends of this and other species over more or less wide-ranging areas. In this thesis effects of weather factors were instead compared between different forest stands from the about same geographical location. The effects of precipitation, temperature and frost on the year ring characteristics of pine were studied in the research forest of Svartberget Vindeln, in northern Sweden. The stands differed in site index and silvicultural treatment; fertile – high stem density, fertile – low stem density, poor – high stem density and poor – low stem density. Drill cores (4 mm) were taken from ten trees in each stand and analysed using X-ray densitometry. Ring width, latewood density, ring density and latewood proportion were compared to weather data from the years 1980 to 1998. The following hypotheses were tested in the stands: i. Precipitation during the summer months does not influence any of the parameters ring width, latewood density, ring density or latewood proportion. ii. Temperature sum after cessation of shoot elongation has a positive effect on latewood density. iii. Frost during the growth period does not influence the development of ring width, latewood density, ring density and latewood proportion. The simple relationships were then analysed with multiple regression analysis. The precipitation sum for the period June – August was found to have a negative effect on latewood density as well as ring density in all four stands. The temperature sum, totally and specifically for the second half of the vegetation period, had a positive impact on latewood density in three stands out of four. The effects on latewood density demonstrated the best concurrent trends between the stands in general; however, in some stands other ...